A Lewis acid activated reaction of Zn with EtI to promote highly enantioselective alkyne additions to aldehydes. Issue 2 (18th November 2014) - Chen, Shan-yong; Liu, Winnie; Wu, Xuedan; Ying, Jun; Yu, Xiaoqi; Pu, Lin
Abstract : Zn powder and EtI in the presence of ( S )-BINOL and Ti(O i Pr)4 promote highly enantioselective alkyne addition to aldehydes at rt to generate chiral propargylic alcohols. Abstract : An easily available BINOL–Ti(O i Pr)4 catalyst system is found to activate the reaction of Zn powder with EtI for the asymmetric alkyne addition to aldehydes at room temperature. It allows the synthesis of a number of synthetically useful chiral propargylic alcohols with both high yields and high enantioselectivity (up to >96% ee).